Phylogeny of European Anodontini (Bivalvia: Unionidae) with a redescription of Anodonta exulcerata. Issue 3 (7th December 2019) - Riccardi, Nicoletta; Froufe, Elsa; Bogan, Arthur E; Zieritz, Alexandra; Teixeira, Amílcar; Vanetti, Isabella; Varandas, Simone; Zaccara, Serena; Nagel, Karl-Otto; Lopes-Lima, Manuel
Abstract: Freshwater bivalves are highly threatened and globally declining due to multiple anthropogenic impacts, making them important conservation targets. Because conservation policies and actions generally occur at the species level, accurate species identification and delimitation is critical. A recent phylogenetic study of Italian mussel populations revalidated an Anodonta species bringing the number of known European Anodontini from three to four species. The current study contributes to the clarification of the taxonomy and systematics of European Anodontini, using a combination of molecular, morphological and anatomical data, and constructs phylogenies based on complete mitogenomes. A redescription of A. exulcerata and a comparative analysis of morphological and anatomical characters with respect to the other two species of Anodonta present in the area are provided. No reliable diagnostic character has emerged from comparative analysis of the morphometric characters of 109 specimens from 16 sites across the Italian peninsula. In fact, the discriminant analysis resulted in a greater probability of correct assignment to the site of origin than to the species. This confirms the difficulties of an uncritical application of visual characters for the delimitation of species, especially for Anodontinae.